Impact of Preoperative and Intraoperative Factors on Postoperative Outcomes in Patients with Colorectal Cancer: A 10-Year Retrospective Study - Lucian Flavius Herlo; Ioana Golu; Alexandra Herlo; Claudia Raluca Balasa Virzob; Ionescu Alin; Stela Iurciuc; Ionut Eduard Iordache; Luana Alexandrescu; Doina Ecaterina Tofolean; Raluca Dumache (Diseases)
Background and Objectives: Colorectal cancer is a major contributor to global cancer morbidity and mortality. Surgical resection remains the cornerstone of treatment, but postoperative complications can significantly affect patient outcomes. Identifying factors that influence postoperative morbidity and mortality is crucial for optimizing patient care. This study aims to evaluate the impact of preoperative, intraoperative, and postoperative factors on surgical outcomes in patients with colorectal cancer. Methods: A retrospective cohort study was conducted on 688 patients who underwent colorectal cancer surgery within a 10-year period. Data collected included demographic information, comorbidities, laboratory values, surgical details, and postoperative outcomes. Statistical analyses were performed using chi-square tests for categorical variables and t-tests for continuous variables. Multivariate logistic regression was used to identify independent predictors of postoperative complications and mortality. Results: Postoperative complications occurred in 28.5% of patients, and the 30-day mortality rate was 5.2%. Preoperative factors such as elevated C-reactive protein (CRP) levels (p < 0.001), low albumin levels (p = 0.003), a high American Society of Anesthesiologists (ASA) score (p < 0.001), and presence of comorbidities like diabetes and hypertension (p = 0.005) were significantly associated with increased postoperative complications. Intraoperative factors such as blood loss greater than 500 mL (p < 0.001) and longer operative time (p = 0.021) were also significant predictors of adverse outcomes. Multivariate analysis identified elevated CRP (OR 2.1, 95% CI 1.5–2.9), low albumin (OR 1.8, 95% CI 1.3–2.5), and blood loss > 500 mL (OR 2.4, 95% CI 1.7–3.4) as independent predictors of postoperative complications. Conclusions: Preoperative inflammatory markers, nutritional status, ASA score, comorbidities, and intraoperative factors like blood loss significantly influence postoperative outcomes in colorectal cancer surgery. Recognizing these risk factors allows for better preoperative optimization and surgical planning, potentially reducing postoperative morbidity and mortality.